A crise do trabalho segundo a abordagem da regulação - Benfica, Fernando de Amorim (2008)
The purpose of this study, based on the methodological and conceptual apparatus of the Regulation Approach (RA), is to present an analysis of the causal mechanisms that ultimately left labour in ruins, labour in its historical form which was hegemonic in the leading capitalist economies during the Golden Age . In order to accomplish that purpose, this work begins with an overview of the theories of crises and end of labour , then proceeds to the examination of the category of labour in its ontological and historical senses. Next, it introduces the methodology developed by the French Regulation School, assessing its analytical capacity to account for the reproduction of social structures, without neglecting their contradictory character, thus avoiding functionalist historical solutions. Applying that method, it analyses the historical constitution of labour settled in the Fordist model of developme nt, in order to discuss the causes of its exhaustion. The conclusion drawn from the analysis is that the so-called crisis of labour constitutes, in fact, a great crisis (in the RA context) of the Fordist model of development, as the contradictory dimensions inherent to one of its fundamental structural forms the wage relation have been fatally aggravated, and also, until now, no other model has been able to take its place, consolidating itself hegemonically.